Assistance for catfish farming using the biofloc method in Tanjungkalang Village, Nganjuk Regency - Achmad Syaichu; Agustin Sukarsono; Denny Kurniawati (Journal of Community Service in Science and Engineering (JoCSE), 2023)
This community service aims to assist fish farmers on how to cultivate fish properly. Good fish farming certainly requires a place for breeding, hatchery, and growing fish. This service aims to assist the community in cultivating catfish using biofloc media. This assistance has an economic impact on the community, namely helping to meet food needs without buying fish at the market. In addition, it is also efficient to make because all the ingredients for fish farming are easy to get and are readily available around the house. This community service activity included a group of fish cultivators (Pokdakan) in Tanjungkalang Village, Nganjuk Regency. This activity results in a biofloc media with specifications of 4 m in diameter and about 0.8 m – 1 m in height. One biofloc can accommodate as many as 4000 catfish seeds. Pengabdian masyarakat ini bertujuan untuk mendampingi petani ikan tentang bagaimana cara membudidayakan ikan dengan baik. Budidaya ikan yang baik tentunya membutuhkan tempat untuk penangkaran, pembenihan, dan pembesaran ikan. Pengabdian ini bertujuan untuk membantu masyarakat dalam membudidayakan ikan lele dengan media bioflok. Pendampingan ini memiliki dampak ekonomis bagi masyarakat yaitu membantu memenuhi kebutuhan makanan tanpa harus membeli di pasar ikan. Selain itu, juga efisien untuk dibuat karena semua bahan pembuatan tempat pembudidayaan ikan mudah didapat dan sudah tersedia di sekitar rumah. Peserta pada kegiatan pengabdian masyarakat ini adalah kelompok pembudidaya ikan (Pokdakan) di Desa Tanjungkalang, Kabupaten Nganjuk. Hasil dari kegiatan ini yaitu sebuah media bioflok yang memiliki spesifikasi yaitu diameter 4 m dan tinggi sekitar 0,8 m – 1 m. Satu bioflok bisa menampung ikan lele sebanyak 4000 benih.